AQUACULTURE PRACTICES IN SMALL MULTIPLE-USE WATER BODIES IN ODISHA, INDIA - BARIK, NAGESH KUMAR (Journal of the Inland Fisheries Society of India, 2021)
Small multiple-use freshwater resources are widely distributed across the country and used for aquaculture in a diverse way in addition to other use like irrigation, sanitations, navigation, etc. The paper makes an assessment of the state of aquaculture in these water bodies in Odisha. The study was conducted in two agro-climatic regions i.e. eastern hill and plateau region and eastern coastal plain regions in the state, covering 83 water bodies in 62 villages during 2011-2013. Various management and technological interventions for aquaculture development were assessed. The average productivity was found to be 317 kg/ha, which was significantly less compared to commercial aquaculture practices. There is considerable scope for increase of fish production through application of scientific aquaculture practices. Key words: Multiple-use water, aquaculture, aquaculture management, Odisha